2014
DOI: 10.1177/1010539514524434
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Homophobia and Reduced HIV Testing Among Men Who Have Sex With Men in China

Abstract: Although previous research has examined barriers and facilitators of HIV testing among men who have sex with men (MSM) in China, few studies have focused on social factors, including homophobia and internalized homophobia. This study utilized data from a global online survey to determine correlates of HIV testing as part of a subanalysis focused on Chinese MSM. Controlling for age, HIV knowledge, number of sexual partners, and other covariates, ever having tested for HIV was significantly correlated with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 25 publications
2
56
2
Order By: Relevance
“…These findings are supported by previous research, which identifies that uptake of HIV interventions may be more challenging for MSM who are not out (Huebner et al, 2002;Pyun et al, 2014;Ross et al 2013b). Huebner et al (2002) identified that when MSM were exposed to an HIV prevention intervention, outness was positively associated with increased consistent condom use while experiences of internalized homonegativity were negatively associated with condom use and self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are supported by previous research, which identifies that uptake of HIV interventions may be more challenging for MSM who are not out (Huebner et al, 2002;Pyun et al, 2014;Ross et al 2013b). Huebner et al (2002) identified that when MSM were exposed to an HIV prevention intervention, outness was positively associated with increased consistent condom use while experiences of internalized homonegativity were negatively associated with condom use and self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that the relationship between outness and sexual risk was dependent on the social group to which sexual identity was disclosed (White & Stephenson, 2014). Previous research also indicates that internalized homonegativity and/ or not being out is associated with exposure to, access, and effectiveness of HIV prevention interventions, with reduced exposure to HIV prevention messaging (e.g., HIV prevention campaigns), reduced HIV testing, lower self-efficacy for condom use, and reduced access and acceptability of preexposure prophylaxis (Ayala et al, 2013;Choi, Lui, Guo, Han, & Mandel, 2006;Huebner et al, 2002;Pyun et al, 2014;Ross et al 2013b;Shoptaw et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…78,81 Much of the stigma measurement for gay men has focused on internalised stigma or internalised homonegativity. [84][85][86][87][88] However, recent studies demonstrating the high levels of experienced and perceived stigma in countries ranging from Europe to Sub-Saharan Africa suggest that internalised stigma is an outcome of lived stigma and may be a proxy for mental health stressors related to this stigma. 80,[89][90][91][92][93] Indeed, mental health issues appear consistently as outcomes of stigma and as a mediating determinant of HIV risks.…”
Section: -69mentioning
confidence: 99%
“…These gaps are particularly true for MSM as evidenced by persistently high HIV prevalence and incidence rates. For MSM, HIV responses at the country level continue to be seriously hampered by daily experiences of stigma, discrimination, violence and criminalization [17][18][19][20]. MSM who live in countries that criminalize homosexuality have higher mean scores on perceived homophobia scales and decreased access to basic HIV services, including access to ART, compared to MSM who live in countries with more supportive legal frameworks [21].…”
Section: Introductionmentioning
confidence: 99%